Pelaksanaan piawaian pembangunan fasiliti penginapan dalam kawasan hutan lindungan di Malaysia - Riry Zaimora, Riry Zaimora (2006)
This thesis is a research with a purpose to observe and evaluate the effectiveness of the implementations of accommodation facility development standard for forest protected area in Malaysia by looking at suitability between building and the surrounding. This thesis also suggests development principles which are more suitable to be used and implemented on existing accommodation facility development in Malaysia. The method used in the research is a combination of qualitative and quantitative. In data analysis, the researcher used the matrix evaluation technique. Basically, this research is divided into four part of frame work. The first part discusses what would be the standard and concept of development in the forest protected area in general. The second part evaluates how far the practice of this standard and concept development is implemented in Malaysia. The evaluation includes site planning and building design. The third part discusses the development principles which are suitable for protected area. The research shows that development in Malaysia all this while do not fully implementing the real development principle and standard. The fourth part of this research offer various suggestions as a guide which can be used in preparing accommodation facility within forest protected area in Malaysia